The influence of student motivation on student achievement in junior high school - Gusman, Dessy Arie; Fitria, Happy; Rohana, Rohana (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to determine and analyze the effect of student motivation on student achievement in Junior High School 40 OKU. This type of research is quantitative. The sample in this study was 96 students of Junior High School 40 OKU. Data were collected using a questionnaire, documentation, and observation. Data were analyzed using the SPSS program. The results of this study suggest that there is an effect of student motivation on student achievement. This paper is expected to be useful for school policymakers in increasing student motivation and student achievement.